(3GSJjYGH GdhLhg GdeecfI aj UfYI GdGUWQdGHs - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s
(3ChdgG (B:s
(3ef CeQ GdGUWQdGH hYedg Ydi CbQH GdWQb s
(3BNQgG (B:s
(3hHJeGe gPg GdBdI Je EfLGR GdhYO HeG hYOJgq s
(3Vef eLehY , JQJjHgG (B: 1s
(3HgG LOGhd hCTcGd JhVjMjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B205s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs